Influence of muscle‐sparing lateral thoracotomy on postoperative pain and lameness: A randomized clinical trial. Issue 6 (15th February 2021) - Nutt, Anna E.; Knowles, Toby G.; Nutt, Neil G.; Murrell, Joanna C.; Carwardine, Darren; Meakin, Lee B.; Chanoit, Guillaume
Abstract: Objective: To assess and compare the magnitude of lameness and level of pain after muscle‐sparing lateral thoracotomy (MSLT) and standard lateral thoracotomy (SLT) in dogs. Study design: Randomized, blinded, prospective clinical study. Animals: Twenty‐eight client‐owned dogs. Methods: The latissimus dorsi muscle was retracted in the MSLT group and was transected in the SLT group. Gait was analyzed with a force plate, and the peak vertical force symmetry index (SI) was calculated within 24 hours before surgery, 3 days postoperatively, and 8 to 12 weeks postoperatively. Symmetry index and pain scores as measured by the Glasgow Composite Measure Pain Scale ‐ Short Form were assessed as primary outcome measures. Results: The SI 3 days postoperatively was lower compared with the preoperative SI value in all dogs, consistent with lameness of the ipsilateral thoracic limb ( P < .001). The absolute differences in preoperative and 3‐day‐postoperative SI provided evidence that this change was 3.1‐fold greater after SLT compared with after MSLT ( P = .009). Pain scores 1 day after surgery were lower after MSLT (1) compared with after SLT (2.5, P < .001). Conclusion: Lateral thoracotomies caused postoperative pain and ipsilateral forelimb lameness, and both were reduced by sparing the latissimus dorsi. Clinical significance: Sparing the latissimus dorsi should be considered to decrease immediate postoperative morbidity in dogs undergoing lateral thoracotomy.